Evaluation of a Multiplex-PCR method for rapid detection of Salmonella Typhimurium and Enteritidis in naturally infected guinea pigs (Cavia porcellus) - Díaz O., Gerardo (2017)
The aim of this study was to evaluate the detection capacity of the Multiplex Polymerase Chain Reaction (PCR) method from non-selective pre-enrichment samples (using target sequences of InvA, fliC and prot6E genes) to diagnose Salmonella Typhimurium and Enteritidis and to determine the concordance between the conventional microbiological detection method which consist of non-selective pre-enrichment, selective enrichment, differential agar isolation and biochemical tests. A total of 111 liver samples from guinea pigs with presumptive diagnosis of salmonellosis, collected in Chancay (Lima) and El Mantaro (Junín), Peru were analyzed. Salmonella Typhimurium was detected by multiplex PCR in 54% (60/111) of the samples and by microbiological analysis in 41% (45/111). A substantial concordance was found with a Kappa value of 0.64. The McNemar test showed that the results of both tests were statistically different (p<0.05).